Impact of a Longitudinal Quality Improvement and Patient Safety Curriculum on Pediatric Residents - Vachani, Joyee G. (Pediatr Qual Saf, 2016)
INTRODUCTION: The effectiveness of longitudinal quality/safety resident curricula is uncertain. We developed and tested our longitudinal quality improvement (QI) and patient safety (PS) curriculum (QIPSC) to improve resident competence in QI/PS knowledge, skills, and attitudes. METHODS: Using core features of adult education theory and QI/PS methodology, we developed QIPSC that includes self-paced online modules, an interactive conference series, and mentored projects. Curriculum evaluation included knowledge and attitude assessments at 3 points in time (pre- and posttest in year 1 and end of curriculum [EOC] survey in year 3 upon completion of all curricular elements) and skill assessment at the EOC. RESULTS: Of 57 eligible residents in cohort 1, variable numbers of residents completed knowledge (n = 42, 20, and 31) and attitude (n = 11, 13, and 37) assessments in 3 points in time; 37 residents completed the EOC skills assessment. For knowledge assessments, there were significant differences between pre- and posttest and pretest and EOC scores, however, not between the posttest and EOC scores. In the EOC self-assessment, residents’ attitudes and skills improved for all areas evaluated. Additional outcomes from project work included dissemination of QI projects to hospital-wide quality/safety initiatives and in peer-reviewed national conferences. CONCLUSIONS: Successful implementation of a QIPSC must be responsive to a number of learners, faculties, and institutional needs and integrate adult learning theory and QI/PS methodology. QIPSC is an initial effort to address this need; follow-up results from subsequent learner cohorts will be necessary to measure the true impact of this curriculum: behavior change and practice improvements.